Π-TYPE FERMIONS AND π-TYPE KP HIERARCHY. (14th September 2018) - WANG, NA; LI, CHUANZHONG
Abstract: In this paper, we first construct π -type Fermions. According to these, we define π -type Boson–Fermion correspondence which is a generalization of the classical Boson–Fermion correspondence. We can obtain π -type symmetric functions S λ π from the π -type Boson–Fermion correspondence, analogously to the way we get the Schur functions S λ from the classical Boson–Fermion correspondence (which is the same thing as the Jacobi–Trudi formula). Then as a generalization of KP hierarchy, we construct the π -type KP hierarchy and obtain its tau functions.